The.Effect.of.Giving.Noni.Fruit.Extract.Microcapsules (Morinda.Citrifolia L.) as.Feed Additive on Blood Cholesterol and Triglyceride Levels in Sentul Chicken - Clarisa Rindiany (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2022)
The purpose of this research was to determine the effect of microcapsules of noni fruit extract as a feed additive to replace AGP on blood cholesterol and triglyceride levels in Sentul chickens.. The research was done from April until July 2022. The method used experimental with a Completely Randomized Design (CRD) and the effect of treatment was using Analysis of Variance then followed by Duncan test. The treatments consisted of 5 types with 4 repetitions, those are P0 = Basal feed that did not contain microcapsules of noni fruit extract, P1 = Basal feed + 50 mg/kg zinc bacitracin, P2 = Basal feed + 125 mg/kg noni fruit extract microcapsules, P3 = Basal feed + 250 mg/kg noni fruit extract microcapsules, and P4 = Basal feed + 375 mg/kg noni fruit extract microcapsules. Samples test was held in Physiology and Biochemistry Laboratory, Animal Husbandry, University of Padjadjaran. The observed variables were blood cholesterol and triglyceride levels. The results showed that the effect of giving noni fruit extract microcapsules non significant effect (P>0.05) on reducing blood cholesterol levels, but was significant (P<0.05) on reducing blood triglyceride levels. The conclusion of the research that giving of noni fruit extract microcapsules as a feed additive with levels of 125 mg/kg could replace AGP in reduce blood triglyceride levels, but could not decrease blood cholesterol levels in Sentul chickens.